A dimensão pedagógica da Tabela Periódica no ensino de conceitos químicos - CUNHA, Mayana Ferreira da (2019)
It is notorious that the periodic table (TP) has been a standard reference, an icon in the field of chemistry, present from the classroom to the most advanced research centers, which contributed to the systematization and organization of scientific knowledge. After all, TP is one of the most brilliant scientific constructs and its broad understanding is of paramount importance for the teaching of chemistry, since its systematization presents the information about the (physical, chemical and (a) periodic) properties of the elements and provides an interface with other chemical contents, the result of the collaboration of various characters in different contexts, through innumerable transformations that reinforced, and still reinforce, that Chemistry is not an absolute and unchanging knowledge, presenting various representations and a constant innovation. However, even in the face of such relevance, the teaching of PT is generally treated under a superficial, anachronistic and decontextualized approach. From the premise that the current teaching of TP privileges theoretical aspects in a complex way, since it is one of the themes that most presents problems for students' learning due to its abstract nature, it is necessary to reflect on how to contribute to learning of the periodic table in chemistry teaching. For the methodological development and with the purpose of answering the guiding question, it was delineated a research with qualitative approach, which was constituted in three stages, being two of analysis and an intermediate corresponding to the development of the educational object in e-book format. . In the first stage of analysis, in the light of the literature, experiences and supported by the interview with chemistry teachers, a study of the indicators on the teaching of the periodic table was conducted. In the second stage of analysis, a questionnaire was applied to the participants to verify the potential of this material in pedagogical practice. Finally, the results of this investigation indicate a remarkable importance of the educational object developed, not only for the teaching of TP, but also for the teaching of other concepts that permeate chemistry.